Young people and the discourse on Aids: from the centrality of context to the appropriation of sense - DOI: 10.3395/reciis.v3i3.286en - Janine Cardoso; Kátia Lerner (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2009)
The text discusses results of a piece of research that analyzed the ways in which young people from two neighborhoods on the outskirts of the city of Rio de Janeiro dealt with risk situations and information about Aids prevention. In other words, how they interpreted, circulated and converted into practice the prevention measures suggested to them. The theoretical perspectives of social discourse semiology and social mobilization were joined, making the symbolic mediations present in these processes stand out, revealing that underneath an apparently homogeneous speech tensions and conflicts exist, such as class, generation and gender conflicts, typical of social relations, and which also manifest themselves in the context of Aids prevention.